Infrastructure and trade in Asia - Brooks, Douglas H.; Menon, Jayant, 1965-; Asian Development Bank. Institute; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2008)
Analysis of infrastructure's role in facilitating international trade and consequently regional economic integration is still rudimentary. This original book fills that knowledge gap by exploring relevant concepts, measurement issues, aspects of the implementation of trade-related infrastructure facilities and their impacts on poverty, trade, investment and macroeconomic balances.
Infrastructure and trade in Asia : an overview / Douglas H. Brooks and Jayant Menon -- A framework for considering infrastructure for regional co-operation / John Weiss -- Trade facilitation : what, why, how, where and when? / Philippa Dee, Christopher Findlay and Richard Pomfret -- Regional co-operation, governance, soft infrastructure and trading costs / Haider A. Khan -- Empirical estimates of trade costs for Asia / Prabir De -- Roads and poverty : a general equilibrium analysis for Lao PDR / Jayant Menon and Peter Warr -- Road infrastructure and regional economic integration : evidence from the Mekong / Christopher Edmonds and Manabu Fujimura -- Meeting the MDG water target in Asia : the role of regional co-operation / P.B. Anand -- Infrastructure financing : impacts on macroeconomic balances / Douglas H. Brooks and Fan Zhai.
"A joint publication of the Asian Development Bank Institute and Edward Elgar Publishing."
Includes bibliographical references and index.
Keywords: Infrastructure (Economics) -- Asia; Asia -- Commerce; Asia -- Economic conditions -- 1945-; Asia -- Economic policy; Electronic books